The improvement of science process skills in prospective biology teacher students through the implementation of feedback - Kasman Arifin; Nurrijal Nurrijal; Jahidin Jahidin; Asmawati Munir; Suriana Gende Ede (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Science process skills (SPS) is a fundamental aspect in science education that enables prospective biology teachers to think critically, analyse data, and develop investigative skills. However, previous studies show that the mastery of SPS among prospective student teachers is still relatively low, so efforts are needed to improve it through appropriate learning strategies. This study seeks to improve the SPS of future Biology educators by integrating laboratory activities, especially focusing on providing feedback. This study used a quasi-experimental design, 84 students were divided into control and experimental groups for comparison. The results of data analysis revealed substantial improvements in students' SPS, especially in formulating titles, hypotheses, and inference through the implementation of feedback. Despite these improvements, there was variability in skill improvement among students. Results showed that the majority of students in the experimental group achieved a moderate level of improvement in SPS, while approximately 50% of students in the control group achieved the same level. However, it should be noted that 16.62% of students in the experimental group and 50% of students in the control group still showed low-level improvement. Future research is recommended to develop innovative learning methods, such as project-based learning and interactive technology, to optimally improve skills. Longitudinal analysis is also needed to understand the long-term impact. The findings confirm the importance of evaluating and strengthening teaching by integrating SPS in the curriculum as well as targeted teacher training. The implications include improving the quality of science education, graduate competitiveness and developing more competent science teachers.Abstrak. Keterampilan Proses Sains (KPS) merupakan aspek fundamental dalam pendidikan sains yang memungkinkan mahasiswa calon guru biologi untuk berpikir kritis, menganalisis data, dan mengembangkan keterampilan investigatif. Namun, studi sebelumnya menunjukkan bahwa penguasaan KPS di kalangan mahasiswa calon guru masih tergolong rendah, sehingga diperlukan upaya peningkatan melalui strategi pembelajaran yang tepat. Studi ini berupaya meningkatkan KPS pendidik Biologi masa depan dengan mengintegrasikan kegiatan laboratorium, terutama berfokus pada pemberian umpan balik. Penelitian ini menggunakan desain kuasi-eksperimental, 84 siswa dibagi menjadi kelompok kontrol dan perlakuan untuk perbandingan. Hasil analisis data mengungkapkan peningkatan KPS siswa yang substansial, terutama dalam merumuskan judul, hipotesis, dan penarikan kesimpulan melalui implementasi umpan balik. Terlepas dari peningkatan ini, ada variabilitas dalam peningkatan keterampilan di antara siswa. Hasil menunjukkan bahwa mayoritas siswa dalam kelompok perlakuan mencapai peningkatan KPS tingkat sedang, sementara sekitar 50% siswa dalam kelompok kontrol mencapai tingkat yang sama. Namun, perlu dicatat bahwa 16,62% siswa dalam kelompok perlakuan dan 50% siswa dalam kelompok kontrol masih menunjukkan peningkatan tingkat rendah. Penelitian selanjutnya disarankan mengembangkan metode pembelajaran inovatif, seperti pembelajaran berbasis proyek dan teknologi interaktif, untuk meningkatkan keterampilan secara optimal. Analisis longitudinal juga diperlukan untuk memahami dampak jangka panjang. Temuan ini menegaskan pentingnya evaluasi dan penguatan pengajaran dengan mengintegrasikan KPS dalam kurikulum serta pelatihan guru yang terarah. Implikasinya mencakup peningkatan kualitas pendidikan sains, daya saing lulusan, dan pengembangan guru sains yang lebih kompeten.